Historical Hinterlands for Religious Freedom in the United Kingdom - Hill, Mark (Studies in Christian ethics, 2020)
The peculiar and particular manner in which freedom of religion is promoted and protected in the United Kingdom owes much to the nation's history. This article offers a highly selective consideration of some of the incidents of history which have shaped or foreshadowed the lived reality of freedom of religion in Britain today. It traces key episodes over past centuries, crudely categorised as the Seven Ages of Religious Liberty.